Evaluasi Penggunaan Kromatografi Lapis Tipis Kinerja Tinggi (KLTKT) Densitometri Silika Gel 60 F254 Pada Penetapan Kadar Vitamin C Yang Terdapat Pada Daging Buah Naga Ungu (Hylocereus polyrhizus) - Ridho Asra; Zulharmita Z; Muhammad Amrul (STIFARM Padang, 2017)
Determination of vitamin C in purple dragon fruit (Hylocereus polyhizus) using High Performance Thin Layer LiquidChromatography (HPTLC) Densitometri with silica gel 60 F254 plate has been studied. The flash of dragon fruit was extracted using methanol by maseration method and the maseration extract was concentrated by using rotary evaporator. Vitamin C was seperated by using HPTLC plate with silica gel 60 F254 as stutionary phase and etanol : acetic acid (9.5 : 0.5) as mobile phase and the Rf was 0.64. The spot was maesured by using TLC-densitometry at 254 nm. The vitamin C content in dragon fruit maesured by using linear reqression y = 1726.9 + 17.8008x, r = 0.992. Limit of detection (LOD) and limit of quantification (LOQ) ware 13.32360 ppm and 44.41201 ppm. Respectively the recovery and RSD were calculated which, were 99.24 % and 7.42 % respectively. The study result showed that vitamin C content was 31.21564 ± 2.58116 ppm.